Peran Kepala Sekolah Madrasah Dalam Meningkatkan Kinerja Pendidikan Di Madrasah Aliyah Negeri 1 Sekayu - Meizal Aji Pratama; Saipul Annur; Asep Rohman (Jurnal Pendidikan Sosial Dan Konseling, 2023)
Knowing the role of the madrasa head in improving the performance of educators at MAN 1 Sekayu and knowing the supporting and inhibiting factors in improving the performance of educators at MAN 1 Sekayu. The researcher took the research object at a state educational institution, namely Madrasah Aliyah Negeri 1 (one) Sekayu. This research focuses on the subject of the role of school principals in improving the performance of educators at Madrasah Aliyah Negeri 1 Sekayu. This type of qualitative research uses a qualitative descriptive approach. Based on the research results, the role of the madrasa head, one of which is as a learning supervisor, has been implemented well by the madrasa head at MAN 1 Sekayu. The strategies used include the strategy of giving rewards to those who excel, the strategy of directly warning teachers who make mistakes, the strategy of accepting suggestions and the strategy of exemplary behavior. Efforts to improve teacher performance include treating teachers as colleagues, not merely as people who are employed. The role of the Madrasah Head in improving the performance of educators at MAN 1 Sekayu: carrying out supervision, carrying out supervision and evaluation, providing direction, guidance and coaching, increasing commitment to work. The strategy of the Head of MAN 1 Sekayu in improving teacher performance: raising enthusiasm for performance, collaborating with other institutions, providing motivation, carrying out persuasive communication. The obstacles are limited facilities, poor teacher commitment, teachers doing other business outside of their official duties, lack of mastery of the material. The challenge of improving teacher welfare.